Barriers to activity engagement in older adulthood: Results of a community survey. (12th August 2022) - Scott, Julia E. T.; Luszcz, Mary A.; Walker, Ruth; Mazzucchelli, Trevor; Windsor, Tim D.
Abstract: Objectives: Losses that occur with age can create barriers to meaningful activity engagement, a crucial aspect of ageing well. Research on this topic is frequently qualitative, with few studies accessing large community samples. This study (a) assessed the frequency specific personal and environmental barriers (such as poor health and limited transport access), identified by older adults in previous research, were endorsed; (b) used latent class analysis (LCA) to identify population subgroups based on combinations of these barriers, and (c) examined associations of subgroups with purpose in life and quality of life. Methods: Four hundred and thirty‐two randomly selected Australian adults aged 65+ years (average age 76.7, 58% female) completed a telephone survey. They were asked whether certain barriers affected engagement and provided data on sense of purpose and quality of life. Results: Physical health/mobility were the most frequently reported barriers, followed by sensory difficulties, financial limitations, and caring responsibilities. The LCA revealed up to three subgroups/classes of participants according to the barriers endorsed. Class 1 had low endorsement of all barriers, including physical health. The majority of Class 2 endorsed physical health barriers and other barriers more frequently than Class 1. Class 3 were comparable to Class 2, but also frequently endorsed community access barriers. Class 1 were younger and reported a greater sense of purpose and higher quality of life. Conclusions: Physical health/mobility barriers to engagement are those most frequently endorsed by older adults. These barriers may increase vulnerability to, or exacerbate the impact of additional barriers, such as sensory difficulties, access to transport and lack of finances.